The lake house [compact disc, unabridged] : a novel - Morton, Kate, 1976- (Bolinda Publishing ; Distributed by Brilliance Audio, 2015)
Living on her family's gorgeous lakeside estate in Cornwall, England, Alice Edevane is a bright, clever, inquisitive, innocent, and precociously talented fourteen-year-old who loves to write stories. One midsummer's eve, after a beautiful party drawing hundreds of guests to the estate has ended, the Edevanes discover that their youngest son, Theo, has vanished without a trace. What follows is a tragedy that tears the family apart, leaving their estate as empty as their broken hearts. Nearly sixty years later, having enjoyed a long, successful career as an author, Alice is now eighty years old and living in London. Theo's case has never been solved, though Alice still harbors a suspicion as to the culprit. Miles away, Sadie Sparrow, a young detective in the London police force, is staying at her grandfather's house in Cornwall. While out walking one day, she stumbles upon the old estate. Her curiosity is sparked, setting off a series of events that will bring her and Alice together.